2013
DOI: 10.2500/ar.2013.4.0064
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Mucocele Formation in the Context of Longstanding Chronic Rhinosinusitis: A Clinicopathologic Series and Literature Review

Abstract: Chronic rhinosinusitis (CRS) can lead to serious long-term adverse sequelae, particularly if left untreated. The aim of this study was to describe a series of intracranial mucoceles (ICMs) that arose in the context of longstanding CRS combined with a review of the pertinent literature. A retrospective chart review was performed on all patients who developed ICMs in association with CRS between 2003 and 2012. The clinical presentation, radiographic features, surgical approach, intraoperative findings, and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Ungünstige Anatomie, seitliche Lokalisation oder ausgeprägte Vernarbung und Osteoneogenese können auch heute Indikationen zu einem externen oder kombinierten Vorgehen bei Stirnhöhlenmukozelen sein [819,823,824]. Eine intrakranielle Ausdehnung ist selten und erfordert in Abhängigkeit von der Ausdehnung und einer etwaigen Duraläsion ein zusätzliches externes Vorgehen [828]. Kieferhöhlenmukozelen werden seltener, da die Caldwell-Luc-Operation, die eine häufige Ursache postoperativer Kieferhöhlenmukozelen darstellt, kaum noch durchgeführt wird.…”
Section: Mukozelenunclassified
“…Ungünstige Anatomie, seitliche Lokalisation oder ausgeprägte Vernarbung und Osteoneogenese können auch heute Indikationen zu einem externen oder kombinierten Vorgehen bei Stirnhöhlenmukozelen sein [819,823,824]. Eine intrakranielle Ausdehnung ist selten und erfordert in Abhängigkeit von der Ausdehnung und einer etwaigen Duraläsion ein zusätzliches externes Vorgehen [828]. Kieferhöhlenmukozelen werden seltener, da die Caldwell-Luc-Operation, die eine häufige Ursache postoperativer Kieferhöhlenmukozelen darstellt, kaum noch durchgeführt wird.…”
Section: Mukozelenunclassified
“…It is theorised in this case that the cat’s unilateral sinonasal obstruction and frontal bony swelling occurred secondary to chronic rhinosinusitis (CRS), a known cause in humans. 1 In this case report, the cat had a long 2-year history of left-sided nasal discharge from a young age and previous testing for FIV/FeLV and Cryptococcus species was negative. Blindly obtained endoscopic nasal biopsies were also consistent with marked neutrophilic and lymphoplasmacytic ulcerative rhinitis.…”
Section: Discussionmentioning
confidence: 75%
“…Frontal sinus mucocele is the most common site of mucoceles; Lee et al. [5] reported that the frontal and ethmoid sinuses are the most common sinuses affected by mucoceles.…”
Section: Discussionmentioning
confidence: 99%